MODERATING ROLE OF BOARD EQUITY OWNERSHIP ON THE RELATIONSHIP BETWEEN FEMALE BOARD, BOARD PROCESS AND COMPANIES’ PERFORMANCE - Arien Anjar Puspitosari; Asna Asna; Andi Nu Graha (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The Oil Palm companies create one of the most significant contributions to Indonesia's economic development. However, company performance in oil palm companies falls short of expectations, which is related to how they are accountable to their shareholders. Thus, the study's objective is to investigate the effects of female directors, board process, and board equity ownership on performance in Indonesian oil palm companies. The findings reveal a connection between female director, board process, and company performance. Furthermore, the moderating role of board equity ownership weakens the link between female director and firm performance. Admittedly, the indirect relationship revealed that board equity ownership strengthens the relations between board process and company performance, especially in Indonesian oil palm companies. According to the author's knowledge, a few studies have been conducted in oil palm companies, and it provides a prominent issue in corporate governance mechanisms, particularly on-board equity ownership, the majority of which is held by family members. Keywords: company performance, board equity ownership, female director, board process